Interaktives geometrisches Konstruieren im virtuellen Raum (mathematica didactica, 2006)
Competences in the generation of geometrical constructions using analog and/or interactive tools are important as part of the competence of methods taught in general mathematical instruction. Adequate three-dimensional constructions were impracticable exceptas mental constructions. Now, however, the tool Cabri 3D, which was developed primarily for school geometry, opens up the possibility of realizing three-dimensional constructions ina virtual space, which gives us a completely new access to synthetic spatial geometry. This contribution will therefore develop elements of a didactics of interactive geometrical constructionin a virtual space in correspondance to the prototypic tool.